TORTILLA MILLET SEBAGAI INOVASI PRODUK TEPUNG MILLET - Rizka Nurdiatin, Rizka Nurdiatin (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to raise the use of local food such as cereals, in this study millet was used as a substitute for wheat flour. The use of millet as food is still rarely found in Indonesia, through new product innovations, namely the use of millet flour substituted with wheat flour in the manufacture of tortillas, it is hoped that it can introduce millet to the public. Millet can be an alternative food for the people of Indonesia because of the easy cultivation and affordable prices. This research method uses R & D (Research and Development) with the 4D (Define, Design, Develop, Disseminate). The test material is in the form of samples from each product, while the testing instruments are experimental forms, validation forms I and II, panelist sensory test forms, and preferred test forms during exhibitions with data analysis techniques. Keywords: tortilla, millet, pangan lokal, serealia